Political women and American democracy - Wolbrecht, Christina; Beckwith, Karen, 1950-; Baldez, Lisa. (New York : Cambridge University Press, 2008)
What do we know about women, politics, and democracy in the United States? The last thirty years have witnessed a remarkable increase in women's participation in American politics and an explosion of research on female political actors, and the transformations effected by them, during the same period. Political Women and American Democracy provides a critical synthesis of scholarly research by leading experts in the field. The collected essays examine women as citizens, voters, participants, movement activists, partisans, candidates, and legislators. The authors provide frameworks for understanding and organizing existing scholarship; focus on theoretical, methodological, and empirical debates; and map out productive directions for future research. Political Women and American Democracy is an invaluable resource for scholars and students studying and conducting women and politics research.
Gender as a category of political analysis in American political development / Gretchen Ritter -- Gender, public opinion, and political reasoning / Leonie Huddy, Erin Cassese, and Mary-Kate Lizotte -- Gender in the aggregate, gender in the individual, gender and political action / Nancy Burns -- What revolution? : incorporating intersectionality in women and politics / Jane Junn and Nadia Brown -- Women's movements and women in movements : influencing American democracy from the "outside"? / Lee Ann Banaszak -- Representation by gender and parties / Kira Sanbonmatsu -- Women as candidates in American politics : the continuing impact of sex and gender / Kathleen Dolan -- Women as office holders : linking descriptive and substantive representation / Beth Reingold -- Theorizing women's representation in the United States / Suzanne Dovi -- Political women in comparative democracies : a primer for Americanists / Lisa Baldez.
Includes bibliographical references (pages 199-249) and index.
Print version record.
eBooks on EBSCOhost
Keywords: Börngen, ...; Universidad Sergio Arboleda; Women -- Political activity -- United States; Femmes -- Activité politique -- États-Unis.; POLITICAL SCIENCE -- Government -- General; POLITICAL SCIENCE -- Government -- National; POLITICAL SCIENCE -- Reference; POLITICAL SCIENCE -- Essays; Women -- Political activity; United States; Politik; Demokratie; Politikerin; Frau; USA; Electronic books; Electronic books